Phytochemicals in Gastrointestinal Nematode Control: Pharmacokinetic–Pharmacodynamic Evaluation of the Ivermectin plus Carvone Combination - Miró, María Victoria; Costa Júnior, Livio M.; Lloberas, María Mercedes; Cardozo, Patricia Alejandra; Lanusse, Carlos; Virkel, Guillermo; Lifschitz, Adrián (Multidisciplinary Digital Publishing Institute, MDPI, 2023)
A wide variety of plant-derived phytochemicals with anthelmintic effects have been described. Most of them have shown activity against parasites in vitro but have not been extensively explored in vivo. The aim of the current work was to study the pharmacokinetic–pharmacodynamic relationship of the combined administration of carvone (R-CNE) and ivermectin (IVM) to lambs. Three trials were conducted to evaluate the pharmacological interaction between R-CNE and IVM in lambs infected with resistant nematodes. Drug concentrations were measured in plasma, target tissues, and H. contortus by HPLC with fluorescent (IVM) and ultraviolet (R-CNE) detection. The effect of both compounds on parasites was estimated by the fecal egg count reduction. Coadministration with R-CNE significantly increased the plasma bioavailability of IVM. R-CNE showed a moderate anthelmintic effect, which was greater on the susceptible isolate of H. contortus. After the combination of R-CNE and IVM as an oral emulsion, both compounds were quantified in H. contortus recovered from infected lambs. However, R-CNE concentrations were much lower than those reported to achieve anthelmintic effects in the in vitro assays. Optimization of the pharmaceutical formulation, dose rate, and administration schedule is needed to take advantage of the intrinsic anthelmintic activity of phytochemicals.